2019
DOI: 10.1128/mbio.01723-19
|View full text |Cite
|
Sign up to set email alerts
|

First Days in the Life of Naive Human B Lymphocytes Infected with Epstein-Barr Virus

Abstract: Epstein-Barr virus (EBV) infects and activates resting human B lymphocytes, reprograms them, induces their proliferation, and establishes a latent infection in them. In established EBV-infected cell lines, many viral latent genes are expressed. Their roles in supporting the continuous proliferation of EBV-infected B cells in vitro are known, but their functions in the early, prelatent phase of infection have not been investigated systematically. In studies during the first 8 days of infection using derivatives… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
120
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(134 citation statements)
references
References 104 publications
(165 reference statements)
6
120
0
1
Order By: Relevance
“…This observation is consistent with previous findings that rapid growth of EBV-infected cells is coupled with an increase in biomass for energy and production of biosynthetic intermediates [24]. Hammerschmidt and colleagues also showed that infected cells did not divide within the first three days of infection but rapidly re-commenced growth at 4 dpi, during EBV infection to naïve human B-cells [25]. Thus, EBV reprogrammed the transcriptome of infected cells during the initial stage of infection even without immortalization, similar to EBV infection of naïve or resting B-cells [15, 25, 26].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is consistent with previous findings that rapid growth of EBV-infected cells is coupled with an increase in biomass for energy and production of biosynthetic intermediates [24]. Hammerschmidt and colleagues also showed that infected cells did not divide within the first three days of infection but rapidly re-commenced growth at 4 dpi, during EBV infection to naïve human B-cells [25]. Thus, EBV reprogrammed the transcriptome of infected cells during the initial stage of infection even without immortalization, similar to EBV infection of naïve or resting B-cells [15, 25, 26].…”
Section: Resultssupporting
confidence: 91%
“…Hammerschmidt and colleagues also showed that infected cells did not divide within the first three days of infection but rapidly re-commenced growth at 4 dpi, during EBV infection to naïve human B-cells [25]. Thus, EBV reprogrammed the transcriptome of infected cells during the initial stage of infection even without immortalization, similar to EBV infection of naïve or resting B-cells [15, 25, 26].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the EBV tegument protein BNLF1 targets ATRX and DAXX for sequestration in PML bodies at this timepoint (23), suggesting that HIRA and newly induced CAF1 may be responsible. H3.1 and H3.3 levels remained stable at Day 4 post-infection, a timepoint at which cells have entered Burkitt-like hyperproliferation and divide every 8-12 hours (1113). Interestingly, after the period of Burkitt-like hyper-proliferation that extends roughly from days 3-7 post-infection, H3.1 and H3.3 levels nearly doubled, even when controlling for increases in EBV genome copy number over this interval.…”
Section: Resultsmentioning
confidence: 99%
“…Incoming EBV genomes are organized into nucleosomes, which must then be maintained or remodeled on newly synthesized, damaged or transcribed regions of EBV genomes. Burkitt lymphoma are amongst the fastest growing human tumor cells, and newly EBV-infected B-cells undergo Burkitt-like hyperproliferation between days 3-7 post-infection in cell culture (1113). Host machinery must therefore propagate chromatin-encoded epigenetic information with each cell cycle, which begins with histone loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation